The Curse of Aid - Djankov, Simeon; Montalvo, Jose G.; Reynal-Querol, Marta (2012)
Foreign aid provides a windfall of resources to recipient countries and may result in the same rent seeking behavior as documented in the "curse of natural resources" literature. In this paper, we discuss this effect and document its magnitude. Using panel data for 108 recipient countries in the period 1960-1999, we find that foreign aid has a negative impact on institutions. In particular, if the foreign aid over GDP that a country receives over a period of 5 years reaches the 75th percentile in the sample, then a 10-point index of democracy is reduced between 0.5 and almost one point, a large effect. For comparison, we also measure the effect of oil rents on political institutions. We find that aid is a bigger curse than oil.